2008
DOI: 10.1176/ps.2008.59.6.627
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and PTSD Among Adolescents With Severe Emotional Disorders Involved in Multiple Service Systems

Abstract: PTSD is a common but underdiagnosed disorder among adolescents with severe emotional and behavioral disorders who are involved in multiple service systems. Routine screening for trauma exposure and PTSD should be conducted with all adolescents receiving mental health services so that treatment can be provided to those with PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 55 publications
2
34
1
Order By: Relevance
“…Pediatric patients with PTSD present with a multitude of symptoms affecting functioning across different domains. Mueser and Taub (2008) reported a rate of PTSD as high as 20% among youth with severe emotional disorders who were involved in multiple systems of care. The authors also reported that adolescents with PTSD were more likely to engage in a variety of high-risk behaviors including running away from home, self-injury, and delinquency.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric patients with PTSD present with a multitude of symptoms affecting functioning across different domains. Mueser and Taub (2008) reported a rate of PTSD as high as 20% among youth with severe emotional disorders who were involved in multiple systems of care. The authors also reported that adolescents with PTSD were more likely to engage in a variety of high-risk behaviors including running away from home, self-injury, and delinquency.…”
Section: Introductionmentioning
confidence: 99%
“…A portion of the variance may be attributable to concerns that current PTSD criteria are insuffi ciently developmentally informed, leading to elevated false-negative rates among children and youth. However, in contrast to general population studies, high rates of PTSD, depression, and developmental and functional impairments were reported consistently in studies of maltreated children, children who experienced traumatic loss and bereavement associated with natural disasters [33,51], and children in other high-risk groups (eg, youth in residential treatment and juvenile detention) [41,42].…”
Section: Discussionmentioning
confidence: 76%
“…Most adolescents with SED experienced domestic violence (51%) and the death of a loved one (51%) [41]. Nearly 50% of this sample had a history of physical abuse, and almost 33% were sexually abused.…”
Section: High-risk Children and Youthmentioning
confidence: 97%
“…In this study the possibility of traumatic events or post-traumatic stress disorder (PTSD) underlying the adolescents' internalizing and externalizing problems, was not considered. There are indications that PTSD is often underdiagnosed (e.g., Mueser & Taub, 2008). It could be the case that group care workers act differently on adolescents who experienced severe trauma, which might explain the lack of a relationship between group care worker behavior and treatment outcome.…”
Section: Discussionmentioning
confidence: 99%